Percepção dos problemas ambientais urbanos a partir do uso de mapas mentais: uma proposta de educação ambiental crítica/emancipatória em escola urbana de Rosário do Sul-RS - Severo, Melina Dornelles (2012)
Environmental problems had intensified with the sedentarization of man and with the modification of the natural landscape or first nature with the emergence and implantation of cities. With the growth of cities also increased environmental problems within the urban environment. The currently standard of many cities is unsustainable due to various reasons such as lack of urban planning, pollution, garbage problem, the irregular housing, lack of sanitation, among many others that could be mentioned. With the emergence of these problems emerges also a constant concern with environmental issues and the preservation of nature. Environmental education arises as an alternative, in an attempt to mitigate the damage caused by man, and also to educate society to care for and preserve the environment, changing its posture with nature and with the use of natural resources, trying to live in a sustainable society. The main objective of this paper was evaluate, from the use of mind maps, how the students from 7th grade at State High School Padre Ângelo Bartelle in the city of Rosário do Sul RS, perceive urban environmental problems. These objectives were achieved by working with the concept of perception in the classroom, discussing the relationship between society and the consumption together with students, and linking it with existent global environmental problems. Afterwards, students confected mental maps which represented the main environmental problems of your living space. The mental maps of the students were analyzed with the aid of the phenomenological method and analysis methodology proposed by Kozel (2001). Based on the analysis of mental maps made by students, it was identified the main environmental issues raised by the students as being the most serious within your living space in the urban environment. Several environmental problems were pointed out by them, but the garbage was the main one. Therefore, it is required a deep Environmental Emancipatory Education work, facing this problem and resuming the pursuit of awareness not for just recycling, but also an attitude toward the consumption and to the search for alternatives that can transform the living space. Keywords: Environmental Problems, Perception, Mental Maps, Environmental Education